2010
DOI: 10.1007/s11104-010-0419-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphorus on growth and cluster-root formation in the Chilean Proteaceae: Embothrium coccineum (R. et J. Forst.)

Abstract: One of the main factors that favours the formation of cluster roots is a low supply of phosphorus (P). The soils of southern Chile are mainly formed from volcanic ash, characterized by low levels of available P. Embothrium coccineum, a Chilean Proteaceae species produces cluster roots (CR). The factors that control CR formation in Chilean Proteaceae have not been extensively studied. The objective of this work was to assess the effects of P on the growth and cluster-root formation of E. coccineum. Plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…An increase in the CRN in P deficiency conditions was observed previously in other experiment using plants of E. coccineum (Zúñiga-Feest et al, 2010). The decreases in all parameters measured in CR of seedling of E. coccineum grown under NPA, suggest that CR induction in E. coccineum could be mediated by basipetal transport of auxin.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…An increase in the CRN in P deficiency conditions was observed previously in other experiment using plants of E. coccineum (Zúñiga-Feest et al, 2010). The decreases in all parameters measured in CR of seedling of E. coccineum grown under NPA, suggest that CR induction in E. coccineum could be mediated by basipetal transport of auxin.…”
Section: Resultssupporting
confidence: 81%
“…These environmental conditions could favor the development of CR in E. coccineum (Donoso, 2006). In addition, a recent report indicates that low P availability induces CR formation in E. coccineum (Zúñiga-Feest et al, 2010). However, little is known about hormonal effects in CR induction in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster roots in crop and pasture plants may well be advantageous, compared with mycorrhizal associations, in soils that have a high level of total P but where most of this is only sparingly available, such as young volcanic soils with low pH (Borie and Rubio, 2003). Examples of Proteaceae on such volcanic soils include Embothrium coccineum in Chile (Zú ñ iga-Feest et al, 2010). Old lateritic soils also contain high levels of occluded P Figure 1.…”
Section: Root Clustersmentioning
confidence: 99%
“…Previous results with E. coccineum showed a rapid carboxylate-exudation rate (citrate, malate) by mature cluster roots (Delgado et al 2014) and a strong acid exudation in cluster roots when they were placed on agar plates with bromocresol purple, where acid exudation is indicated by a change in colour from purple to yellow (Zúñiga-Feest et al 2010). Results of this study showed a decrease in the pH in the rhizosphere of mature cluster roots compared with that during other developmental stages and, even though we did not determine the rate of carboxylate exudation by cluster roots at different development stages in the present study, we measured [P] and [Mn] in these root tissues which can be used as an indirect measurement of the release of these organic compounds, because these mobilise P (through ligand exchange and/or complexation of metal ions binding P) and micronutrients such as Mn (through high chelating and reductive capacity of some organic acids).…”
Section: Discussionmentioning
confidence: 92%